Laws of Nature and Explanatory Circularity - Castro, Eduardo (2019)
Some recent literature [Hicks, M. T. and van Elswyk. P., (2015) pp. 433-443, 2015; Bhogal, H. (2017), pp. 447-460] has argued that the non-Humean conceptions of laws of nature have a same weakness as the Humean conceptions of laws of nature. That is, both conceptions face an explanatory circularity problem. The argument is as follows: the Humean and the non-Humean conceptions of laws of nature agree that the law statements are universal generalisations; thus, both conceptions are vulnerable to an explanatory circularity problem between the laws of nature and their instances. In this paper, I argue that Armstrong’s necessitarian view of laws of nature is invulnerable to this explanatory circularity problem.